Modulation of Neuron and Astrocyte Dopamine Receptors via Receptor-Receptor Interactions - Diego Guidolin; Cinzia Tortorella; Manuela Marcoli; Chiara Cervetto; Raffaele De Caro; Guido Maura; Luigi F. Agnati (MDPI AG, 2023)
Dopamine neurotransmission plays critical roles in regulating complex cognitive and behavioral processes including reward, motivation, reinforcement learning, and movement. Dopamine receptors are classified into five subtypes, widely distributed across the brain, including regions responsible for motor functions and specific areas related to cognitive and emotional functions. Dopamine also acts on astrocytes, which express dopamine receptors as well. The discovery of direct receptor-receptor interactions, leading to the formation of multimeric receptor complexes at the cell membrane and providing the cell decoding apparatus with flexible dynamics in terms of recognition and signal transduction, has expanded the knowledge of the G-protein-coupled receptor-mediated signaling processes. The purpose of this review article is to provide an overview of currently identified receptor complexes containing dopamine receptors and of their modulatory action on dopamine-mediated signaling between neurons and between neurons and astrocytes. Pharmacological possibilities offered by targeting receptor complexes in terms of addressing neuropsychiatric disorders associated with altered dopamine signaling will also be briefly discussed.